Effect of the methanol extract of the Lion's Mane mushroom, Hericium erinaceus, on bone metabolism in ovariectomized rats - N. Morita; H. Matsushita; A. Minami; S. Shimizu; R. Tachibana; H. Kanazawa; T. Suzuki; K. Watanabe; A. Wakatsuki (IMR Press, 2020)
Purpose: Osteoporosis is a major health concern in postmenopausal women. The aim of the study was to investigate the effect of Hericium erinaceus (H. erinaceus), also known as the Lion's Mane mushroom, consumption on bone metabolism in ovariectomized (Ovx) rats. Materials and Methods: Rats in the Baseline group were sacrificed immediately, whereas rats in the Sham group underwent sham surgery, and those in the Ovx and Ovx + HE groups underwent bilateral Ovx. A diet containing the methanol extract of H. erinaceus was given to the Ovx+HE group for 13 weeks. Results: There was no significant difference in the femoral bone mass between the Ovx and Ovx+HE groups. In the histomorphometric study of the proximal tibial metaphysis, the osteoblast surface, mineralizing surface, and fat cell number were lower in the Ovx+HE group than those in the Ovx group. Conclusion: The present findings suggest that H. erinaceus does not prevent but rather accelerates bone loss in Ovx rats.